Islamic Self-efficacy: Building the Competence of Human Development - Lusiantia, Dina; Fachrunnisa, Olivia (inovator, 2024)
The readiness of human resources is the most critical support in developing halal tourism. Competence of human resources as strength. Several studies have used social cognitive theory in building human competence. However, it is rare to use a social cognitive theory approach to work as worship. This study aims to determine the achievement of human development competencies in Halal Tourism. This study uses a social cognitive theory approach with Islamic values, namely Islamic Self-Efficacy. The number of samples in this study was 96 respondents who came from the tourism-driving community in Terban Kudus. The analysis used multiple regression with SPSS to test the effect of Islamic self-efficacy on human resource competence. As a result, it is known that the behavior of believing in destiny, halal knowledge, and workplace spirituality simultaneously and partially affect the competence of halal tourism ambassadors. This study reveals the existence of Islamic Self-efficacy in building human resource competence in the field of halal tourism.